(untitled) - Yager, Joseph A. (Washington, D.C., 1984)
This book explain the changes in energy supply and use that occurred in Northeast Asia during the 1960s and 1970s
Keywords: Power resources,Energy policy,Chính sách năng lượng,Nguồn điện; Economic aspects,Khía cạnh kinh tế; East Asia,East Asia,Đông Nam Á,Đông Nam Á